Safety, Sensory Quality and Nutritional Value of Hybrid Meat Products Made from Turkey Meat and Red Beans Preserved with a Bioprotective Culture - Małgorzata Karwowska; Patrycja Skwarek; Elżbieta Solska; Agata Nowaczyk; Andrzej Goławski; Przemysław Wojtaś; Dariusz M. Stasiak (Molecules)
The current study assessed the quality and safety of hybrid meat products made from turkey meat and red beans with the addition of SAFEPRO® B-LC-20 protective cultures. The tested materials were hybrid products produced with turkey thigh muscles and red beans in 100:0, 60:40, 50:50 and 40:60 ratios. During a 15-day storage period, research was carried out on the physicochemical and microbiological properties, antioxidant capacity, fatty acid profile and sensory characteristics. The results showed that the count of Enterobacteriaceae in hybrid meat products did not differ significantly depending on the formulation. The addition of red beans in a hybrid meat product formulation significantly increased the antioxidant activity of the products compared to a sample made of 100% meat. The samples with red beans were characterized by significantly lower values of n-6/n-3, UFA/SFA and PUFA/SFA compared to samples produced with turkey thigh muscles and red beans in a ratio of 100:0. In summary, the formulation combining turkey meat and beans in a ratio of 60:40 is recommended as optimal, enabling the creation of a safe hybrid meat product with properties similar to those of a full-meat product.